Protection Of the Creative Idea in Intellectual Property: Within the Anglo-Saxon, Roman, and Latin Systems - et.al, Nashat Mahmoud Jaradat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent times, a relatively modern financial industry has appeared in the Arab world, the so- called venture capital, and the truth is that this financial industry is based mainly on seizing ideas that may be economically feasible in the future and investing in them before they idea formed on the ground of reality, and this is called (the seed investment phase). This stage means that venture capital provides the necessary environment for the creative idea to flourish by providing the necessary infrastructure, such as consultations in the field of marketing, market studies, and finance the idea in order to transform it into reality, in addition to many other things in exchange for obtaining some shares equal to a specific percentage to be agreed upon (sweat equity). So, the idea turns from an abstract idea to a company or a tangible physical reality, and here is the second stage of this type of investment, the so-called (construction phase). At this stage, the company develops its work and starts searching for investors to increase its capital, whether individual investors or those investment funds related to an institution, up to the so-called (exit stage). This type of investment depends on the rise in the shares' market value in which the venture capital invested when it was just an idea (the seed investment phase). Up to the exit stage, in which the value of shares doubles dramatically if the idea succeeds. This face means that the venture investor puts his shares for sale – the one he obtains in return for his services and initial investment in the seed stage - and exit the company. The truth is that this type of investment, although it has been present in developed countries for quite a while, it is relatively new in the Kingdom of Bahrain, as this type of investment requires an infrastructure to flourish. The first business incubator was established in Bahrain in 2015- which has been followed by a group of incubators- suffered from a set of problems represented in the structure of Bahraini laws that do not match the idea's nature. Also, the complexity of procedures. In 2020 we noticed the legislator's direction to correct these matters and prepare the appropriate ground by amending some Bahraini trade laws. The Bahraini legislator added and allowed a set of things that go in the same direction, such as allowing an increase in capital to introduce a strategic partner. They meant by (strategic partners) who can provide quality service such as economic and administrative consultations, expertise in some fields, and providing the necessary environment to succeed.